Organoleptic Qualities of Retort Processed Commercial Paneer Butter Masala Vs in-House prepared Paneer Butter Masala - C.V.Vithun; N.Karpoora Sundara Pandian; K.Kamaleeswari; I.Manikkavasagan; M. Naveenkumar (The Indian Veterinary Journal, 2024)
India, a leading milk producer, faces challenges with milk spoilage due to limited refrigeration. Paneer, a value added product rich in protein and minerals, offers a solution but has short shelf-life due to its higher moisture content (55 -60 % w.b.). Thepresentstudy was attempttodevelop the retort processed paneer butter masala using hot air dried paneer slices and the consumer preference of the in-house prepared paneer butter masala was conducted. The plain gravy for the paneer butter masala was prepared. The paneer was made from buffalo milk and cut to the specified dimensions of (20 mm × 20 mm × 5 mm) and was dried to the moisture content of 16.44 % (d.b.) in tray dryer. The dehydrated paneer slices were added with the plain gravy. The rehydration of paneer slices was done through the retort process. The sensory evaluation was done using the 9-point hedonic scale. The commercial paneer butter masala had overall acceptability (7.0526±0.32) scores that compared favorably with the overall acceptability (7.3158±0.27) scores of in-house preparedpaneer butter masala. The sensory scores were revealed that the in-house paneer butter masala was found superior to the commercially available paneer butter masala with respect to the sensory score of the organoleptic panel. Hence, the inventory cost of in-house retort processed paneer butter masala is minimized due its ambient storage whereasthe fresh paneer demands refrigerated storage. The commercial use of retort processed paneer butter masala will be the promising future to foodindustry.